Multiple coordination and quaternary states of fish hemoglobin re-open the Root effect question - MAZZARELLA, LELIO; VERGARA, ALESSANDRO; MERLINO, ANTONELLO; L. Vitagliano; C. Verde; G. di Prisco (2008)
The Root effect is a widespread property in fish hemoglobins (Hbs) that produces a drastic reduction of cooperativity and oxygen-binding ability at acidic pH. Up to now, the structural explanation of the Root effect has been based on the two-state model, and is related to an over-stabilization of the T quaternary structure. Here, we report the crystal structure of the deoxy and carbomonoxy form of the non-Root effect major component Hb isolated from the Antarctic fish Trematomus newnesi (Hb1Tn). In the deoxy state, the inter-aspartic hydrogen bond at the α1β2 interface between Asp95α and Asp101β is observed. In the carbomonoxy Hb1Tn crystals, both a T-like state and a R/T intermediate quaternary structure are observed. In these crystals, three of four independent CO coordination states are not assisted by the hydrogen bond with the distal histidine, that goes out of the heme pocket. This un-assisted CO coordination states are associated with unusually small thermal fluctuations which characterise both α and β CD corners. The accessibility of ligated states within three different quaternary structure (T, R and R/T intermediate) suggests a novel structural explanation of protein allostery based on a three state Edelstein’s model.